Contesting Ethnic and Religious Identities in the 2019 Indonesian Elections: Political Polarization in West Kalimantan - Qodir, Zuly; Jubba, Hasse; Hidayati, Mega (Studia Islamika, 2022)
During Indonesia’s 2019 presidential election, significant religious and ethnic contestations occurred using hatred and stigma in expressing support for favored candidates. This article focuses on the case of West Kalimantan Province which has a divided society and memories of ethnic-based bloody communal violence in the early 2000s.  This article notifies that wherein ethnic Dayak, Javanese, and Chinese voters tended to support Joko Widodo (Jokowi)-Ma’ruf Amin, while ethnic Malay, Madurese, and Buginese voters tended to back Prabowo Subianto-Sandiaga Uno up in the election. However, such ethnic and religious contestations in West Kalimantan did not generate violent conflicts during the election. Instead, voters continued to interact peacefully and harmoniously among different ethnic and religious groups. This contestation coincided with the emergence of political awareness among the Dayaks, Chinese, and Malays of West Kalimantan, which further contributed to Jokowi’s electoral victory.  Nevertheless, this political contestation produced the political identity.